Pengaruh Sumber Pengetahuan Konsumen Non-Business Controlled terhadap Keputusan Penggunaan Direktori Kuliner Online Zomato (Jurnal Manajemen dan Organisasi, 2019)
The rises of the culinary industry in Indonesia nowadays has opened opportunities for startup developers to create online culinary directories platforms. One of popular online culinary directories or well known by online restaurant searcher in Indonesia is Zomato. To formulate Zomato’s promotional strategies, a study is needed on the sources of knowledge that can not be controlled by the company (non-business controlled). Based on this problem, the aims of this study are to identify the Zomato user characteristics and the relation with Zomato use decisions, to idenitify a relevant consumer sources of knowledge, to analyze it, and, to know its effect on Zomato use decisions. This study uses primary data and secondary data. This study is using logistic regression as analytical model. The result of this study shows that Zomato user is dominated by 16-25 age single woman. Most of them are student and lives in Jakarta. Average income of them are